Digital Transformation of Halal MSMEs: Sharia Compliance Practices within the Marketplace Ecosystem in Pacitan Regency - Catur Wahyono (Golden Ratio of Data in Summary, 2026)
Digital transformation presents both opportunities and challenges for halal MSMEs, particularly as marketing activities shift into marketplace ecosystems that operate with competitive mechanisms, promotional strategies, and algorithms different from conventional trading practices. This study aims to explain the experiences of halal MSME actors in Pacitan Regency in undertaking digitalization processes while maintaining Sharia compliance in digital marketing activities. Employing a qualitative phenomenological approach, data were collected through in-depth interviews, on-site and digital observations, and documentation, and then analyzed using the Miles, Huberman, and Saldaña model. The findings indicate that MSME actors utilize marketplaces such as Shopee and Tokopedia to expand market reach; however, varying levels of digital literacy lead to the use of platform features being largely limited to basic functions. From the perspective of Sharia compliance, some MSMEs strive to maintain transparency in product information and uphold the principle of amanah (trustworthiness), yet gaps remain between halal claims and formal certification, alongside ethical dilemmas arising from promotional pressures imposed by platforms. Key challenges include technological limitations, restricted access to certification, and limited understanding of Sharia values within the context of digital marketing. This study underscores the need for regional ecosystem support through Sharia-based digital training, facilitation of halal certification, and strategic collaboration among local governments, MSME facilitators, and marketplace providers. These findings contribute empirical evidence to strengthen the literature on the digitalization of halal MSMEs and its implications for Sharia business practices in non-metropolitan regions.